Raff. A History of Germany from the Medieval Empire to the Present - Luehrs, Robert (Teaching History: A Journal of Methods, 1991)
To be effective a textbook must exhibit readability, coherent structure, conciseness without superficiality, and consistency of viewpoint; it should also provide adequate discussion of the evolution and significance of events so that students acquire insight without being overwhelmed by the complexities of each topic. Raff’s German history, in uncluttered translation by Bruce Little, for the most part has these attributes.